2018
DOI: 10.1098/rspb.2018.0542
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive learning and memory in hybrids as a reproductive isolating barrier

Abstract: Selection against hybrid offspring, or postzygotic reproductive isolation, maintains species boundaries in the face of gene flow from hybridization. In this review, we propose that maladaptive learning and memory in hybrids is an important, but overlooked form of postzygotic reproductive isolation. Although a role for learning in premating isolation has been supported, whether learning deficiencies can contribute to postzygotic isolation has rarely been tested. We argue that the novel genetic combinations crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 84 publications
(186 reference statements)
0
34
1
Order By: Relevance
“…In several taxa, learning is known to play a role in mate choice (e.g., sexual imprinting and learned avoidance of heterospecific mates) and thus can potentially be linked to prezygotic isolation (Dukas, ; Servedio, Sæther, & Sætre, ; Verzijden et al, ). Learning and memory have also been linked to postzygotic isolation since deficiencies in these traits can be selected against in hybrids (Rice & McQuillan, ). Recently, McQuillan, Roth, Huynh, and Rice () found that hybrid chickadees scored lower than parental chickadees in associative spatial learning and problem‐solving tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In several taxa, learning is known to play a role in mate choice (e.g., sexual imprinting and learned avoidance of heterospecific mates) and thus can potentially be linked to prezygotic isolation (Dukas, ; Servedio, Sæther, & Sætre, ; Verzijden et al, ). Learning and memory have also been linked to postzygotic isolation since deficiencies in these traits can be selected against in hybrids (Rice & McQuillan, ). Recently, McQuillan, Roth, Huynh, and Rice () found that hybrid chickadees scored lower than parental chickadees in associative spatial learning and problem‐solving tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The improved LMC caused by Wolbachia may be favorable for flies to find food and escape from dangerous environments. Evidence has suggested that LMC is likely to be important for fitness in a diverse set of taxa (Rice & McQuillan, 2018). For example, in grasshopper Schistocerca americana, insects that could employ associative learning had exhibited higher growth rates than insects that were prevented from learning (Dukas & Bernays, 2000).…”
Section: Effect Of Wolbachia On Learning and Memory Capacity (Lmc) Inmentioning
confidence: 99%
“…One 445 would therefore find it likely that in this particular case of divergence, behavioural traits would 446 be affected in a similar way. diverging populations [18,76]. Although the hybrids from our experiment did not differ the two 453 morphs in their average behavioural responses, they tend to show reduced repeatability in the 454 traits for which the two morphs show high level of consistent individual differences.…”
mentioning
confidence: 58%
“…85Despite the recent conceptual advances about the importance of personality in the processes of 86 adaptive divergence and speciation, empirical studies directly investigating it are still lacking 87[14]. Information is especially lacking regarding the behavioural phenotype of hybrids and 88 their contribution to reproductive isolation [18]. 89…”
mentioning
confidence: 99%
See 1 more Smart Citation